Ragam Bahasa Slang Pada Kata “Well” - Dimas Pramana Putra; Abian Rajiv Setyawan (Student Scientific Creativity Journal, 2023)
In the 21st century, there are many uses of new and foreign language terms, not even a few of these language terms have become normalized or normalized by the community for use in everyday life. The problem contained in this study is that the use of the slang term "well" is more dominantly used on social media, especially on social media tiktok and especially young people who tend to understand more about the term "well" slang. The purpose of this research is to find out why in the 21st century people, especially young people, are more interested in using the slang term "well" for everyday use and especially in social media tiktok. And also to invite or get used to using Indonesian more often . The method used in this research is qualitative data. The results of this study are to prove why the younger generation is more likely to use and understand more the Indonesian language in social media because Indonesian itself is an identity for citizenship. Based on the results of research that in the 21st century, people, especially the younger generation, are more comfortable and easier to understand the slang term "well".